Adaptive Fuzzy and Robust H∞ Compensation Control for Uncertain Robot - Yuan Chen; Guangying Ma; Shuxia Lin; Jun Gao (Institute of Advanced Engineering and Science, 2013)
In this paper, two types of robust adaptive compensation control schemes for the trajectory tracking control of robot manipulator with uncertain dynamics are proposed. The proposed controllers incorporate the computed-torque control scheme as a nominal portion of the controller; an adaptive fuzzy control algorithm to approximate the structured uncertainties; and a nonlinear H∞ tracking control model as a feedback portion to eliminate the effects of the unstructured uncertainties and approximation errors. The validity of the robust adaptive compensation control schemes is investigated by numerical simulations of a two-link rotary robot manipulator